Endovascular thrombolysis for massive cerebral venous thrombosis in a teenager with nephrotic syndrome. - Costa, Paula (2010)
Cerebral venous thrombosis is a rare but potentially severe condition in children. We present the case of a teenager with corticodependent nephrotic syndrome diagnosed at five months of age and treated with cyclosporine A. In the context of recurrence of nephrotic syndrome he presented with headache, vomiting and severe intracranial hypertension. While the raised intracranial pressure and the status epilepticus were controlled, the brain imaging revealed venous thrombosis of all venous sinus, with absence of venous drainage. He was submitted to local thrombolysis with recombinant tissue plasminogen activator, with recanalization of the venous sinuses. The outcome was favourable, without neurological deficits. In this case, the early radiologic intervention was crucial, enabling a full neurological recovery, in a teenager whose initial prognosis was very poor.